The matter as a language. From redundancy to concealment - Espuelas, Fernando (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2015)
It is always next to us in silence. Like those good, attentive and discrete servants, it does not seem to have life of its own. The matter of architecture is all around us; it protects us at all times. It has been entrusted to give us shelter and comfort. It is something that comes before anything else, what we sense in it before we even feel its effects. If we pay attention to it, it seems to be willing to express itself by means of its own nature. Hans Georg Gadamer says that “that which can be understood is language”. It would be said then, that the language of the matter is one with no strict code which doesn’t use unequivocal signs. The matter intones a language which is both historic and obscure, and at the same time, ancestral and recondite.